Secured Transmission of EEG Signals Using Wireless Medical Sensor Network - Shanthi Kumaraguru , Dr.M.R. Ebenezar Jebarani (International Journal of Advanced Science and Technology, 2020)
Wireless Device Networks (WSN) is an emerging technology with the ability to reshape human life’s approach. Applications for health care are promising areas for the Wireless Medical Sensor Network, wherever medical sensors are often used to track patient health. Wireless Medical Sensor Networks (WMSNs) are the main sanctioning technology in healthcare applications which allow wearable biosensors to collect information about the essential body parameters of a person. The main concern in the field of Biometric Cryptosystems is to guarantee the privacy and integrity of secret data. The art of encrypted data known as cryptography serves the protection of data information transmission. In communication networks, biometric cryptography is the growing technique. Numerous types of square biometry measure usable for coding and cryptography in addition. This paper introduces a new technique known as cryptography of the brain wave. This paper proposes a technique for transmitting EEG data in an extremely secure manner. Using high-pass filtering, the pre-processing of the EG signal is completed. Using honey cryptography, the signal is encrypted to create a secure data. Instead, by creating a key system, the encrypted data is retrieved as an original knowledge.